2010
DOI: 10.1002/ldr.1036
|View full text |Cite
|
Sign up to set email alerts
|

Some characteristics of organic soils irrigated with municipal wastewater

Abstract: Soil irrigation with wastewater (WW) gives the opportunity to solve the problems of its disposal, final purification or reuse. Many studies have examined mineral soils upon continued WW application. The aim of this paper was to examine the properties of organic soils 3 years after WW application was discontinued. Peat-muck soil planted with Populus spp. or Salix spp., and mineral-muck soil under grasses were irrigated for 4 years with municipal WW at a low (comparable with intensive NPK fertilization) and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…The tendency of the increase in BD, Clm, and Clw is an indication of the effects of tillage and the higher application of inorganic fertilizer than Clw and other land-uses (Table 3). The results are in line with the findings of [27][28][29][30][31], which revealed that the BD of the soil surface layers could be reduced with no tillage compared to conventional tillage; and this study showed that the BD in the soil surface layers of AAO, GL, CAO, and SGL were slightly lower compared to Clm and Clw.…”
Section: Physicochemical Properties Of the Soil In The Different Landsupporting
confidence: 91%
See 1 more Smart Citation
“…The tendency of the increase in BD, Clm, and Clw is an indication of the effects of tillage and the higher application of inorganic fertilizer than Clw and other land-uses (Table 3). The results are in line with the findings of [27][28][29][30][31], which revealed that the BD of the soil surface layers could be reduced with no tillage compared to conventional tillage; and this study showed that the BD in the soil surface layers of AAO, GL, CAO, and SGL were slightly lower compared to Clm and Clw.…”
Section: Physicochemical Properties Of the Soil In The Different Landsupporting
confidence: 91%
“…This is perhaps due to slightly higher WSA, GMD, and MWD in AAO and GL compared to the other types of land use. Similarly, according to the AAO and GL soil data, a slightly lower BD, higher WSA, MWD, GMD, and SOC in AAO and GL is due to less soil disturbance and higher SOM [27,29,31,37,40,[56][57][58]. …”
Section: Differences In Soc Between Different Land-use Systemsmentioning
confidence: 78%
“…At this location, soil was classified as a peatmuck (Terric Histosol), according to the FAO classification. The basic soil properties were as follows: organic matter (OM) content 30.3-47.9%; pH 7.80-9.13 (in CaCl 2 ); bulk density 0.307-0.627 mg m -3 (Brzezińska et al, 2011). The experimental area was divided into two plots of 1 hectare area.…”
Section: Methodsmentioning
confidence: 99%
“…The species composition of an active sludge organisms may also inform about possible malfunction of wastewater treatment plant biological part [3,5,14,15]. A safe use of dewatered sewage sludge, for example for agricultural application or recultivation of degraded areas, also depends on presence of heavy metals [16][17][18] and pathogenic organisms [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The species composition of an active sludge organisms may also inform about possible malfunction of wastewater treatment plant biological part [3,5,14,15]. A safe use of dewatered sewage sludge, for example for agricultural application or recultivation of degraded areas, also depends on presence of heavy metals [16][17][18] and pathogenic organisms [19][20][21].Particle diameter measurements can be conducted in many ways, and the most basic and the first to be applied were the microscope observation methods [11,12,22,23]. Neis and Tiehm used, among others, the membrane filtration method.…”
mentioning
confidence: 99%